Ethnobotany of plant in the mopat asam ritual of dayak limbai tribe, tanjung beringin village - Ege, Benediktus; Bustami, Yakobus; Utami, Yuniarti Essi; Anjelina, Anjelina (STKIP Persada Khatulistiwa Sintang, 2026)
The Dayak Limbai tribe is one of the indigenous communities that still strongly uphold traditions and local wisdom in their daily lives. One such tradition is the Mopat Asam ritual, a customary ceremony related to pregnancy and the birth of a first child, which carries deep spiritual and social significance. Plants play an important role in this ritual, as they are believed to have symbolic, spiritual, and functional value. The purpose of this study is to identify the types of plants used and how they are utilized in the Mopat Asam ritual. This research was conducted using a descriptive qualitative method through survey techniques and data collection using interview sheets. Data analysis was carried out using a qualitative approach. The results of the study show that there are 18 plant species from 9 families used in the Mopat Asam ritual, with the Zingiberaceae family being the most dominant.